2016
DOI: 10.1111/ddi.12487
|View full text |Cite
|
Sign up to set email alerts
|

Spread rates on fragmented landscapes: the interacting roles of demography, dispersal and habitat availability

Abstract: Aim We still lack a comprehensive understanding of the relative importance of demographic, dispersal and landscape characteristics on species' rates of range expansion (RRE) and on how these factors interact. Here, we provide an analysis of these effects for passive dispersers, by investigating how habitat characteristics, such as habitat quality, availability and fragmentation, interplay with species' dispersal characteristics in determining species' RRE. In addition, we assessed the predictability of RRE in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…Because female sea otters exhibit strong site fidelity and typically are poor pioneers (Tinker et al 2008b, Lafferty andTinker 2014), large gaps in kelp forests along the range fronts present a substantial obstacle to natural range expansion. Full recovery of the California sea otter may require consideration of management strategies that overcome marginal habitats and population sinks along the range edges, perhaps by increasing the rate of female dispersal (Barros et al 2016) to more sheltered habitats that could support reproduction and act as a source to repopulate areas farther north. In addition to fostering recovery, sea otter population expansion along its historic range would enhance restoration of both wetland and nearshore coastal habitats throughout California.…”
Section: Discussionmentioning
confidence: 99%
“…Because female sea otters exhibit strong site fidelity and typically are poor pioneers (Tinker et al 2008b, Lafferty andTinker 2014), large gaps in kelp forests along the range fronts present a substantial obstacle to natural range expansion. Full recovery of the California sea otter may require consideration of management strategies that overcome marginal habitats and population sinks along the range edges, perhaps by increasing the rate of female dispersal (Barros et al 2016) to more sheltered habitats that could support reproduction and act as a source to repopulate areas farther north. In addition to fostering recovery, sea otter population expansion along its historic range would enhance restoration of both wetland and nearshore coastal habitats throughout California.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when these species are introduced into a new region, whether intentionally or accidentally (Gozlan et al 2010a), the data available for predicting their invasiveness are often limited (Top et al 2018), resulting in poorly informed model parameters (Heikkinen et al 2014;Urban et al 2016) and final models with high uncertainty (Parry et al 2013). We showed that monitoring programmes can provide dispersal time series that, when coupled with ABC methods, can help overcome this lack of prior data, enabling more robust predictions of the dispersal dynamics and future invasiveness of the modelled species (Neeson et al 2012;Barros et al 2016;Samson et al 2017).…”
Section: Model Insights Into Bitterling Dispersalmentioning
confidence: 95%
“…In this scenario, the heterogeneous spatial pattern of climate change regimes may mimic classical habitat mosaics, with some regions being more hospitable to particular genotypes than others (Barros et al 2016). In general, dispersal across heterogeneous landscapes is more difficult than across homogeneous ones, with patterns of local adaptation exacerbating this disparity (Zhang and Buckling 2016).…”
Section: Asynchronous Regimes Dispersal and Intra-specific Variatiomentioning
confidence: 99%
“…Our simulated landscape was evenly populated, and only varied in one habitat parameter -climate asynchronicity. Natural habitat matrices are far more complex and it is unlikely that even the most abundant species are distributed evenly across their range (Barros et al 2016). Similarly, the genetic architecture of our simulated quantitative trait was simplistic.…”
Section: Spatial Heterogeneity In Climate Change Regimes Limits Dispementioning
confidence: 99%